(untitled) (Pragya Darshan प्रज्ञा दर्शन, 2025)
This study presents a comprehensive assessment of the weather, climate, and air quality conditions at the KSAFTER (Kushechaur Simriklek Agrimed Forest Tourism Education and Research) site in Putalibazaar-2, Syangja District, Gandaki Province, Nepal. Using secondary data from January 2023 to early 2024, sourced from the Department of Hydrology and Meteorology (DHM), Accuweather, and other online platforms, the study analyzed monthly variations in temperature, atmospheric pressure, relative humidity, wind speed, rainfall, sunshine duration, and cloud cover. Results indicate distinct seasonal patterns characteristic of Nepal’s mid-hill subtropical climate. Winters were dry and cool (low of 1.4°C in January), while the monsoon months (June–August) brought peak humidity (82%), maximum rainfall (347 mm in July), and the lowest atmospheric pressure (1005.5 mbar). Wind speeds peaked during the pre-monsoon (7.5 km/h in April), while sunshine hours were highest from March to May. In addition to climatic parameters, the study evaluated real-time air quality using the Air Quality Index (AQI). Pollutants such as PM2.5, PM10, O₃, NO₂, SO₂, and CO were monitored using publicly available data. AQI readings in Putalibazaar generally ranged between "Fair" and "Good," with localized fluctuations. On 14th November 2024, the AQI was recorded within the “Fair” category (20–49). These findings provide an essential environmental baseline for agroforestry, eco-tourism, and land-use planning at the KSAFTER site and offer a scalable model for climate-smart development in similar Himalayan mid-hill regions.